2011
DOI: 10.1016/j.smrv.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nocturia on sleep

Abstract: Sleep plays a vital role in physical and mental functioning. It is increasingly recognized that disturbed sleep is a highly prevalent and chronic condition that merits greater awareness due to the wide-ranging and serious repercussions associated with it. Nocturia is one of the causes of sleep disturbance and has been shown to impair functioning, quality of life, health and productivity, with those experiencing two or more voids per night reporting significant ‘bother’. Nocturia warrants full consideration as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 60 publications
2
76
0
8
Order By: Relevance
“…In addition, there was no difference between African Americans and Whites on RLS measures, which agrees with some studies 14,15,31,32 but not all. 11,33 Given that there is a link between sleep problems and health outcomes, we also explored the relationship of sleep with disability. Like sleep complaints, disability is common in older adults, with approximately 35%-50% of older adults having some difficulties with activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there was no difference between African Americans and Whites on RLS measures, which agrees with some studies 14,15,31,32 but not all. 11,33 Given that there is a link between sleep problems and health outcomes, we also explored the relationship of sleep with disability. Like sleep complaints, disability is common in older adults, with approximately 35%-50% of older adults having some difficulties with activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that poorer sleep quality and shorter sleep durations are associated with impairments in physical functioning, 9,10 and daytime consequences of insomnia include weakness and fatigue. [10][11][12] Unfortunately, most subjective sleep problems have been determined from general health surveys or with limited sleep measures, and almost all studies have been done in the majority White population. In the relatively few studies that have been conducted in diverse studies, African Americans have been found to have a higher prevalence of sleep disturbances than Whites, [13][14][15] including being more susceptible to developing sleep disordered breathing.…”
Section: Introductionmentioning
confidence: 99%
“…Nocturia, commonly known as one of the lower urinary tract symptoms (LUTS), is also a common sleep related complaint among older adults, [1][2][3][4][5] with two or more nocturia episodes per night reported by over 30% of the elderly. [6][7][8][9] Multiple factors contribute to the high prevalence of nocturia among older men.…”
Section: Introductionmentioning
confidence: 99%
“…Uma boa noite de sono, desempenha um papel fundamental no bem-estar físico, psíquico e social dos indivíduos, é também benéfica para o cérebro, exerce influência no bom funcionamento da memória e na capacidade de absorção de informação portanto, dormir bem é essencial para quem estuda. (Ancoli-Israel et al, 2011). Sobre o uso do Cinto de segurança  2 : p≤ 0,000.…”
Section: Tratamento De Dadosunclassified